The Lactococcus lactis Pan-Plasmidome - Kelleher, Philip; Mahony, Jennifer; Bottacini, Francesca; Lugli, Gabriele A.; Ventura, Marco; van Sinderen, Douwe (Frontiers in Microbiology, 2019)
Plasmids are autonomous, self-replicating, extrachromosomal genetic elements that are typically not essential for growth of their host. They may encode metabolic capabilities, which promote the maintenance of these genetic elements, and may allow adaption to specific ecological niches and consequently enhance survival. Genome sequencing of 16 Lactococcus lactis strains revealed the presence of 83 plasmids, including two megaplasmids. The limitations of Pacific Biosciences SMRT sequencing in detecting the total plasmid complement of lactococcal strains is examined, while a combined Illumina/SMRT sequencing approach is proposed to combat these issues. Comparative genome analysis of these plasmid sequences combined with other publicly available plasmid sequence data allowed the definition of the lactococcal plasmidome, and facilitated an investigation into (bio)technologically important plasmid-encoded traits such as conjugation, bacteriocin production, exopolysaccharide (EPS) production and (bacterio)phage resistance.